Investigating the Mediatory Role of Self-Efficacy Beliefs in the Relationship between Self-Perception, Peer Support, and Subjective Well-Being in Visually Impaired Teenagers - Nazari 1, Leila; Bakhtiarpour 1*, Saeed; Naderi 1, Farah; Heidari 1, Alireza (Shahroud Journal of Medical Sciences, 2020)
Background: Subjective well-being is considered as one of the most important measures for the health of a society, and it refers to emotional improvement to be able to enjoy life. The main objective of the current study was to investigate the mediatory role of self-efficacy beliefs in the relationship between self-perception, peer support, and subjective well-being in visually impaired teenagers. Methods: The study was a descriptive correlation performed by path analysis. The statistical population included all female students with visual impairment in Kermanshah city and 176 of which were selected as the sample of the study using convenience sampling. The research instruments included Ryff's Psychological Well-Being Scales (PWB), the Self-Concept Scale, the Peer Support Questionnaire, and Self-Efficacy Beliefs Questionnaire. The proposed model was evaluated using path analysis with AMOS software. Results: The results showed that all the direct paths, except for the path from self-perception to subjective well-being, were significant (P= 0.0001). Moreover, the indirect paths through self-efficacy beliefs to subjective well-being were also significant (P= 0.0001). Conclusions: According to the results of the study, the proposed model had a good fit, and is an important step in identifying the factors affecting the subjective well-being of adolescents with visual impairment. Keywords: Visual impairment, Subjective well-being, Self-perception, Peer support, Self-efficacy beliefs.